Small mode volume plasmonic film-coupled nanostar resonators. Issue 6 (12th May 2020) - Charchi, Negar; Li, Ying; Huber, Margaret; Kwizera, Elyahb Allie; Huang, Xiaohua; Argyropoulos, Christos; Hoang, Thang
Abstract : Individual plasmonic film-coupled nanostar resonators exhibit polarized optical modes in ultrasmall volumes, which can be useful for applications in sensing or enhanced light-matter interactions. Abstract : Confining and controlling light in extreme subwavelength scales are tantalizing tasks. In this work, we report a study of individual plasmonic film-coupled nanostar resonators where polarized plasmonic optical modes are trapped in ultrasmall volumes. Individual gold nanostars, separated from a flat gold film by a thin dielectric spacer layer, exhibit a strong light confinement between the sub-10 nm volume of the nanostar's tips and the film. Through dark field scattering measurements of many individual nanostars, a statistical observation of the scattered spectra is obtained and compared with extensive simulation data to reveal the origins of the resonant peaks. We observe that an individual nanostar on a flat gold film can result in a resonant spectrum with single, double or multiple peaks. Further, these resonant peaks are strongly polarized under white light illumination. Our simulation data revealed that the resonant spectrum of an individual film-coupled nanostar resonator is related to the symmetry of the nanostar, as well as the orientation of the nanostar relative to its placement on the gold substrate. Our results demonstrate a simple new method to create an ultrasmall mode volume and polarization sensitive plasmonic platform which could be useful for applications in sensing or enhanced light–matter interactions.